The fin-de-siècle culture of adolescence - Neubauer, John, 1933-2015 (Yale University Press, 1992)
Preoccupation with adolescence was one of the hallmarks of European culture at the turn of the century. In this absorbing book, John Neubauer examines the representation of adolescents in the literature, visual arts, psychology, and psychoanalytic theory of this period, and he considers the social institutions and youth movements that were formed to accommodate them. Neubauer argues that the depiction of adolescence in art and literature did not merely reflect its emergence as a middle-class phenomenon of industrial societies but helped to shape its social construction as well. Neubauer's discussion of adolescents in literature begins with the inner lives of some adolescent protagonists (Stephen Dedalus, Tonio Kroger and Young Torless) as told by adult narrators. His focus then becomes wider, moving to the adolescent as viewed by a peer-narrator, to the adolescent's cliques and gangs, and to the gardens, schools, and streets in which the narratives of adolescence are set. In the second half of the book he treats nonliterary subjects. Neubauer considers portrayals of adolescents by such artists as Munch, Kirchner, Heckel, Kokoschka, and Schiele. He discusses the narrative construction of Freud's case history of Dora and the problems of female adolescence in Horney's Adolescent Diaries, as well as questions of gender and homosexual identity in turn-of-the-century psychological theories of adolescence. The final chapters consider adolescence in school, church, the German Wandervogel, and the Boy Scouts, focusing on the literary and rhetorical means involved in institutionalizing adolescence.